The Effect of Transformational Leadership and Employee Placement on Work Engagement of Civil Servants with Job Satisfaction as an Intervening Variable - Purba, Melisanra; Sule, Ernie Tisnawati; Soemaryani, Imas (Jurnal Maksipreneur, 2023)
This study aims to analyze and understand the influence of Transformational Leadership and Employee Placement on the Work Engagement of Millennial Generation Civil Servants. with Job Satisfaction as an Intervening Variable. This study employs survey research techniques along with a descriptive and quantitative verification strategy. The population in this study consisted of 813 Millennial Civil Servants of the Ministry of Finance in Bandung City, and a sample size of 269 persons was used. A questionnaire was employed for primary data collection, and SmartPLS 3.2 software was used to analyze the data using a structural equation model (SEM) based on variance or partial least squares (PLS). According to the study's findings, transformational leadership significantly and favorably impacts job satisfaction. Job happiness is positively and significantly impacted by employee placement. Work engagement is positively and significantly impacted by job satisfaction. Engagement at work is positively and significantly impacted by transformational leadership. Work engagement is significantly and favorably impacted by employee placement. Through job happiness, transformational leadership dramatically and favorably influences work engagement. Through job satisfaction, employee placement has a favorable and considerable impact on work engagement.